Molecular screening of rare cucurbit accessions for the presence of markers for genes and QTls controlling resistance to powdery mildew - E. N. Markova; F. A. Berensen; I. V. Gashkova; O. Yu. Antonova (Труды по прикладной ботанике, генетике и селекции, 2025)
Powdery mildew (Podosphaera xanthii (Castagne) Braun & Shishkoff ) is considered the most common disease of cucurbitaceous crops, especially in the northwestern and southern regions of Russia. For example, in Krasnodar Territory, the largest domestic squash producer, the damage from powdery mildew reaches 20–40%, which leads to significant economic losses. A possible solution to this problem is to increase the resistance of host plants to pathogens by introducing resistance genes from wild species or rare crop relatives, since other options, including the use of fungicides, can disrupt ecosystems and harm living organisms. Marker-assisted molecular breeding techniques make it possible to quickly identify necessary DNA fragments in order to find resistant and susceptible forms of donor plants. Assuming the presence of original genes for resistance to powdery mildew in rare cucurbits, we conducted molecular screening of 50 sponge gourd (Luffa cylindrica M. Roem.), 50 bottle gourd (Lagenaria siceraria (Molina) Standl.), and 10 Cucumis sp. accessions from the VIR collection for the presence of 15 markers of powdery mildew resistance genes known for widespread and rare cucurbitaceous crops, and clarified the effectiveness of 3 molecular markers.